Graphene facilitated visible light photodegradation of methylene blue over titanium dioxide photocatalysts - Liu, Shi Zhen; Sun, Hongqi; Liu, Shaomin; Wang, Shaobin (Elsevier BV, 2013)
Several graphene–titania composites (G–TiO2) were synthesized by a sol–gel method using titanium isopropoxide (or P25) as Ti-precursors and reduced graphene oxide (RGO). The structural, morphological, and physicochemical properties of the samples were thoroughly investigated by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FE-SEM), UV–vis diffuse reflectance (UV–vis DRS), and thermogravimetric-differential thermal analysis (TG-DTA). A significant increase in light absorption to visible light was observed by G–TiO2 compared with that of naked TiO2. The photocatalytic activity of G–TiO2 in methylene blue bleaching under visible light (>430 nm) is much enhanced. G–TiO2 synthesized from titanium isopropoxide hydrolysis presented higher activity than that of G–TiO2(P25). Contribution of graphene on the enhancement of visible-light photocatalytic activity of the composite was discussed.